The problem of expertise in knowledge societies - Grundmann, Reiner (Springer Verlag, 2016)
This paper puts forward a theoretical framework for the analysis of expertise and experts in contemporary societies. It argues that while prevailing approaches have come to see expertise in various forms and functions, they tend to neglect the broader historical and societal context, and importantly the relational aspect of expertise. This will be discussed with regard to influential theoretical frameworks, such as laboratory studies, regulatory science, lay expertise, post-normal science, and honest brokers. An alternative framework of expertise is introduced, showing the limitations of existing frameworks and emphasizing one crucial element of all expertise, which is their role in guiding action.